Syria from reform to revolt. - Hinnebusch, Raymond A.; Zintl, Tina (Modern intellectual and political history of the Middle East., 2015)
"When Bashar al-Asad smoothly assumed power in July 2000, just seven days after the death of his father, observers were divided on what this would mean for the country's foreign and domestic politics. On the one hand, it seemed everything would stay the same: an Asad on top of a political system controlled by secret services and Baathist one-party rule. On the other hand, it looked like everything would be different: a young president with exposure to Western education who, in his inaugural speech, emphasized his determination to modernize Syria. This volume explores the ways in which Asad's domestic and foreign policy strategies during his first decade in power safeguarded his rule and adapted Syria to the age of globalization. The volume's contributors examine multiple aspects of Asad's rule in the 2000s, from power consolidation within the party and control of the opposition to economic reform, co-opting new private charities, and coping with Iraqi refugees. The Syrian regime temporarily succeeded in reproducing its power and legitimacy, in reconstructing its social base, and in managing regional and international challenges. At the same time, contributors clearly detail the shortcomings, inconsistencies, and risks these policies entailed, illustrating why Syria's tenuous stability came to an abrupt end during the Arab Spring of 2011. This volume presents the work of an international group of scholars from a variety of disciplinary backgrounds. Based on extensive fieldwork and on intimate knowledge of a country whose dynamics often seem complicated and obscure to outside observers, these scholars' insightful snapshots of Bashar al-Asad's decade of authoritarian upgrading provide an indispensable resource for understanding the current crisis and its disastrous consequences."--Back cover